COMMON STUDENTS’ GRAMMATICAL ERRORS IN ARGUMENTATIVE ESSAY WRITING - Safra Apriani Zahraa; Aswandi Aswandi (INOVISH JOURNAL, 2016)
Abstract: Grammar is one of important aspects in learning English. Most students faced difficulties in applying correct grammar in their writing. This study aimed to find out common students’ grammatical error in writing. This research was a descriptive research. This study showed that the most common students’ grammatical error is in the use of preposition with the percentage 36.8%. The error was commonly caused by the interference from their first language (interlanguage error) and the students’ problems inherent within the target language. Keywords : Grammar, Errors